eHealth Interventions for Anxiety Management Targeting Young Children and Adolescents: Exploratory Review - Tozzi, Federica; Nicolaidou, Iolie; Galani, Anastasia; Antoniades, Athos (My University, 2018)
Advances in technology are progressively more relevant to the clinical practice of psychology and mental health services generally. Studies indicate that technology facilitates the delivery of interventions, such as cognitive behavioral therapy, in the treatment of psychological disorders in adults, such as depression, anxiety, obsessive-compulsive disorder, panic symptoms, and eating disorders. Fewer data exist for computer-based (stand-alone, self-help) and computer-assisted (in combination with face-to-face therapy, or therapist guided) programs for youth.
Keywords: Adolescent; Anxiety disorders; Child; eHealth; Mobile applications; Review; Telemedicine